Variation in movement patterns of an elite women soccer player in international matches - Hewitt, A.; Lyons, K. (7th World Congress on Science and Football (WCSF), 2011, 2011)
This study examined the variation in movement patterns of a single player in multiple international women`s soccer matches using a GPS player-tracking device. Methods The subject (Ht: 165.5 cm, Wt: 58.2kg) participated in 11 international women`s soccer games over an 18-month period. The subject wore a MinimaxX athlete-tracking device (Catapult Innovations, Scoresby, Australia, V2.4) in each of these games. Field-based fitness testing comprising: 20m sprint test, vertical jump and a multi stage shuttle test were performed during the data collection period. Results Table 1 provides descriptive results for the movement patterns in each of the 11 international matches. The averages for the fitness testing results were as follows: 20m sprint test: 3.31±0.15s, vertical jump: 51.5±cm & multi-stage shuttle test (Estimated V O2max): 61.1±1.5 ml/kg/min). Table 1 reports the final outcome of each match and the opponents FIFA World Ranking at the time of the match. Discussion & Conclusion This study provides detailed information about one player in international competition, and provides contextual information about each match (final score and FIFA ranking of the opposing team). It is intended to stimulate discussion about the preparation of players for competition. The use of a single subject design raises important questions about the role of case studies in the observation and analysis of performance in football.